Recent evidence for warmer and drier growing seasons in climate sensitive regions of Central America from multiple global datasets. (9th August 2021) - Stewart, Iris T.; Maurer, Edwin P.; Stahl, Kerstin; Joseph, Kenneth
Abstract: Smallholder livelihoods throughout Central America are built on rain‐fed agriculture and depend on seasonal variations in temperature and precipitation. Recent climatic shifts in this highly diverse region are not well understood due to sparse observations, and as the skill of global climate products have not been thoroughly evaluated. We examine the performance for several reanalysis and satellite‐based global climate data products (CHIRPS/CHIRTS, ERA5, MERRA‐2, PERSIANN‐CDR) as compared to the observation‐based GPCC precipitation dataset. These datasets are then used to evaluate the magnitude and spatial extent of hydroclimatic shifts and changes in aridity and drought over the last four decades. We focus on water‐limited regions that are important for rain‐fed agriculture and particularly vulnerable to further drying, and newly delineate those regions for Central America and Mexico by adapting prior definitions of the Central American Dry Corridor. Our results indicate that the CHIRPS dataset exhibits the greatest skill for the study area. A general warming of 0.2–0.8°C·decade −1 was found across the region, particularly for spring and winter, while widespread drying was indicated by several measures for the summer growing season. Changes in annual precipitation have been inconsistent, but show declines of 20–25% in eastern Honduras/Nicaragua and in several parts of Mexico. Some regions most vulnerable to drying have been subject to statistically significant trends towards summer drying, increases in drought and aridity driven by precipitation declines, and/or a lengthening of the winter dry season, highlighting areas where climate adaptation measures may be most urgent. Abstract : Over the past four decades, precipitation trends are the main driver of drought trends, with temperature trends playing a small role. The most widespread drying and increases in aridity have occurred during the summer growing season. Based on delimitations of water‐limited and climate‐sensitive regions (brown shading) that are important for rain‐fed agriculture, some of these highly vulnerable regions overlap with areas of significant drying (red), highlighting potential prioritization areas for climate adaptation measures.